New model for the prediction of visual outcomes in young children with mechanical ocular conditions and comparison with other models - Shreya Shah; Mehul Shah; Ruhi Gunay; Apeksha Kataria; Sakshi Makhloga; Mrugesha Vaghela (Indian Journal of Ophthalmology, 2022)
Purpose: Herein, we compared the efficacy among the Ocular Trauma Score (OTS), Toddlers Ocular Trauma Score (TOTS), and Pediatric Ocular Trauma Score (POTS) for prognosis prediction in Indian children who had mechanical ocular conditions causing traumatic cataract. Methods: This prospective, interventional study recruited consecutive children undergoing operation for traumatic cataracts caused by mechanical eye injuries at Drashti Netralaya. The following details were obtained from their medical files: the circumstance and time of injuries, penetrating injury type, initial and final visual acuity (VA), time of operation, and associated eye diseases. Specific variables were employed to determine the OTS, TOTS, and POTS. For all patients, the final and predicted VA determined using all scores were compared using Fischer's exact test. Accuracy, specificity, and sensitivity were evaluated for all the scores by using the area under receiver operating characteristic curve. Results: We enrolled 124 eyes. Patients' mean value for age was 4.6 ± 1.29 years; 44 (35.41%) and 74 (64.5%) were female and male patients, respectively. Visual outcomes significantly improved after operation, and the outcomes did not differ between closed- and open-globe injuries (P = 0.162). The actual and predicted VA did not exhibit a statistically significant difference among the three scores. TOTS and POTS were more suitable for evaluating low-risk injuries, whereas the OTS could more efficiently examine high-risk cases. Conclusion: TOTS and POTS were more accurate than the OTS in VA prediction after operation in toddlers with traumatic cataracts caused by mechanical globe injury. TOTS and POTS were more suitable for evaluating low-risk injuries, whereas the OTS could more efficiently examine high-risk cases. All the examined scores can be helpful in estimating VA following treatment.